Delegation of Authority in Islamic Education - Eldarifai, Eldarifai; Martin Kustati; Nana Sepriyanti; Izzi Fekrat (International Journal of Education, Vocational and Social Science, 2024)
The leader is a figure who seeks to empower all the resources available at the institution. The research approach using literature review with data from scientific journal references is a method commonly used in scientific research. The results of this study As the manager of the institution, there are many mandates and duties that must be fulfilled, thus requiring the delegation of duties and authority to available human resources. As a religion that is syamil wal mutakammil, it provides guidance in carrying out the mandate and delegation to parties who are competent and have relevance to the assigned tasks. The results of this study indicate that the delegation of authority must fulfill the principle that authority is given to a figure who is able to carry it out, given clear instructions and the importance of evaluating the delegation process given.